PENGEMBANGAN WISATA EDUKASI BERKELANJUTAN: STUDI KASUS DI MUSEUM RADYA PUSTAKA - Bartolomeus Herawan Mintardjo (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2022)
Radyapustaka Museum is oldest museum and popular destination for educational tourism. But there are various obstacles so that in the implementation, educational tourism in Radyapustaka Museum has not been optimal so that need for the development of sustainable educational tourism model that can benefit both the visitors of the museum and the museum. Methods in this study using qualitative methods. Qualitative methods are used to obtain data based on factual conditions that occur, field observations, interviews and literature studies. The results in this study resulted in a new model for sustainable education in the Museum of Radyapustaka which refers to museum education policies, education and sustainable tourism indicators.